Lenguaje comprensivo y los procesos lectores en estudiantes de 7mo año E.G.B de laUnidad Educativa “San Juan Bautista”, 2023-2024 - Celi Malacatus., Daniela Fernanda (2024)
The research titled "Comprehensive Language and Reading Processesin 7th Grade E.G.BStudents at the 'San Juan Bautista' Educational Unit, 2023-2024" focused on analyzing comprehensive language in the reading processes of seventh-grade students at the San Juan Bautista Educational Unit, Catamayo canton, during the 2024 period. A psychopedagogical intervention was designed to improve these skills. A qualitative methodology was employed, using inductive, analytical, synthetic, and descriptive methods. The research encompassed a population of 30 students and 1 teacher, selecting a sample of 3 students and the teacher for detailed analysis. Data collection techniques included semi-structured interviews and directobservations, using validated interview scripts and observation forms. The design was non- experimental. The results showed that seventh-grade students had significant difficulties inidentifying explicit facts and applying critical reading strategies. Finally, it was concluded that specific vocabulary development programs and critical reading instruction are necessary to improve comprehensive language and reading processes, recommending continuous teachertraining to effectively address these areas.